EFFLURAGE MASSAGE AGAINST LABOR PAIN WHEN IN ACTIVE PHASE - Sefrina Rukmawati; Nur Aini Fatimah (Master of Public Health Program Universitas STRADA Indonesia, 2025)
Childbirth is a physiological process that is often accompanied by significant pain, especially in the active phase of the first stage. This pain can affect the physical and psychological condition of the mother, which in turn can affect the labor process itself. One non-pharmacological intervention that can be used to reduce labor pain is the efflurage massage technique. This study aims to explore the effectiveness of efflurage massage in reducing labor pain in the active phase of the first stage. Using a quantitative approach with an experimental design, this research involved 30 pregnant women who were undergoing labor, who were divided into two groups, namely the treatment group and the control group. There are two variables in the research, namely efflurage massage and labor pain. The instrument used is Pain Observation. Statistical tests use the T Test. The results showed that there was a significant reduction in the level of labor pain in the group that received efflurage massage compared to the control group. The average VAS score before the intervention in the efflurage massage group was 7.5, while after the intervention it decreased to 4.2. In contrast, the control group showed little change, with a mean VAS score before intervention of 7.3 and after intervention being 6.8. Statistical analysis shows that this difference is significant with p < 0.01. These findings suggest that the efflurage massage technique may be an effective alternative for labor pain management. Efflurage massage was proven to be effective in reducing labor pain in the active phase of the first stage, with significant results in reducing pain scores compared to the control group. These findings support the idea that non-pharmacological interventions, such as massage, can be a safe and effective alternative for pain management during labor. Thus, it is important for healthcare professionals to consider implementing this technique in their daily practice Keywords: Efflurage Massage, Nyeri, Kala I